E-Commerce Practice in the Light of Mashlahah Mursalah - Khadijatul Musanna (Journal of Islamic Economics Lariba, 2022)
Technology has now become a vessel that plays a role in meeting the needs of people's lives from various fields, especially in many sectors of the real economy. Since the emergence of e-commerce, there have been many conveniences for sellers and buyers in meeting their daily needs. This convenience is the initial foundation of Maslahah Al-Mursalah. This study aims to examine e-commerce from the perspective of Maslahah Al-Mursalah. The research methodology used is descriptive qualitative. Sources of data collected are based on primary and secondary data. The research results obtained in this study are e-commerce practices from the perspective of sharia contracts have similarities with As-salam practices. Through this e-commerce, many benefits can be obtained. So it can be seen that muamalah activities, such as buying and selling bai' as-salam contained in e-commerce practices, are a type of maslahah (convenience/providing benefits) at the level of maslahah hajiyyat.